"Sarmishsoy" talismans - O`roqova Nilufar Azamatovna (Zien Journals, 2022)
This article partially covers the study of rock paintings of the Sarmishsay State Museum-Reserve, the history of painting, the essence of the paintings, the culture, lifestyle and natural resources of the people of that time.
Keywords: Petroglyph; ethnic culture; ethnoculture